Cold Load and Storage Functional Backfill for Cooling Deep Mine - Mei Wang; Lang Liu; Liu Chen; Xiaoyan Zhang; Bo Zhang; Changfa Ji (Advances in Civil Engineering)
Considering the deep mining heat-hazard problem, the concept and academic idea of cold load and storage (CLS) functional backfill applied on deep mine cooling was put forward. Firstly, according to characteristics of filling mining, a method of cooling stopes with CLS phase changing backfill which is made from the backfill material with CLS phase change material (PCM) was proposed. The working process, cooling physics, and the economic and safety benefits of CLS phase changing backfill were produced. Secondly, the theory system of cooling with CLS phase changing backfill was built. The theoretical basis of the key problems involved was investigated and analyzed which concluded heat transfer, fluid mechanics, and backfill mechanics. Lastly, the technology system of cooling with CLS phase changing backfill was established on the basis of the required technical assistance. It includes four parts: the backfill material design, the backfill material conveying way design, the stope temperature control scheme design, and the strength of cemented tailings backfill analysis. The idea of applying CLS phase changing backfill on cooling deep mine stopes and its theory and technology systems provide a scientific research and suitable development direction for deep mine cooling.